Limited Short-Term Benefits Of Glacial Rock Flour For Enhancing The Physical Quality Of Tropical Arable Soils - Obour, P.B.; Dietzen, C.; Danso, E.O.; Arthur, E.; Adu, M.O.; Rosing, M.T. (European Journal of Soil Science, 2024)
There is increasing recognition that the application of fine-grained silicate rock granulates can improve soil productivity by increasing its fertility and amelio rating its physical properties. Although the former has been extensively stud ied, empirical information on the latter is scarce. Pot and field experiments were conducted at the University of Ghana's Forest and Horticultural Crops Research Centre (FOHCREC), Kade, Ghana, from May 2020 to December 2021 to quantify the short-term effect of the application of Greenlandic glacial rock flour (GRF) on the physical properties of three benchmark arable soils in Ghana, namely an Acrisol (sandy clay loam), a Haplic Ferralsol (sandy loam), and an Arenosol (sand). The pot experiment included three GRF treatments (0, 10, and 20 t ha 1 ) and the three soil types, while the field experiment was conducted on only the sandy clay loam soil where GRF rates of 10 and 50 t ha 1 were compared to the control. Intact 100 cm3 soil cores were sam pled from the soil surface in the field and pot experiments to assess the soil bulk density. We also quantified soil water retention, air and gas transport, and pore morphological characteristics over a range of matric potentials. Both the pot and field experiments showed that adding GRF did not improve soil water retention. Still, the response of gas transport and pore characteristics to changing matric potential was significantly (p < 0.05) modified by GRF in some soil types. The results suggested that the effectiveness of the use of GRF to ameliorate soil physical conditions for plant growth may depend on soil type and the soil water matric potential. We concluded that the application of GRF cannot be relied upon as a short-term strategy to significantly improve the structural quality of the tropical soils studied. Rather, GRF should be consid ered for application to the soils for its other beneficial effects. We recommend that the effects of repeated applications and further build-up of the material in the soil should be investigated to determine the effect of higher relative GRF concentrations on soil hydro-physical properties.
Research Article
Keywords: Air Permeability; Enhanced Rock Weathering; Glacial Rock Flour; Pore Size Distribution And Morphological Characteristics; Relative Gas Diffusivity; Soil Water Retention